2008
DOI: 10.1093/ee/37.5.1280
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Obligate Migratory Flight Behavior in Young European Corn Borer (Lepidoptera: Crambidae) Females

Abstract: European corn borer, Ostrinia nubilalis, flight behavior was examined in laboratory experiments. Adults were each tethered to 1 of 16 round-about flight mills in an environmental chamber, and the data were relayed to a computer. Parameters analyzed included duration, distance, and speed of the longest continuous flight and total flight time during an 8-h night. Comparisons were made between unmated and mated adults of both sexes at different ages up to 5 d after emergence. For unmated females, duration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 78 publications
(125 reference statements)
3
48
0
Order By: Relevance
“…Adults are typical migrants with great ßight potential and a relatively long prereproductive period Li 1993b, Cao et al 2006). Adult migration usually occurred before ovarian maturation (Feng et al 2004), which was also observed in other pyralid species such as Cactoblastis cactorum and Ostrinia nubilalis (Dorhout et al 2008, Sarvary et al 2008a. Adults can ßy continuously for 24 h and have ßown a maximum distance Ͼ100 km in a 24-h tethered-ßight test (Luo and Li 1992).…”
mentioning
confidence: 78%
“…Adults are typical migrants with great ßight potential and a relatively long prereproductive period Li 1993b, Cao et al 2006). Adult migration usually occurred before ovarian maturation (Feng et al 2004), which was also observed in other pyralid species such as Cactoblastis cactorum and Ostrinia nubilalis (Dorhout et al 2008, Sarvary et al 2008a. Adults can ßy continuously for 24 h and have ßown a maximum distance Ͼ100 km in a 24-h tethered-ßight test (Luo and Li 1992).…”
mentioning
confidence: 78%
“…But the argument of improved mixing of adults in a blended refuge field does not apply to species where significant dispersal from the natal plant occurs before mating. For example, young European corn borer, Ostrinia nubilalis, females disperse long distances before mating [59], a behavior common among many Lepidoptera, especially migratory species.…”
Section: Spread Of Resistance During Species Invasion or Range Expansionmentioning
confidence: 99%
“…An exception is a study by Showers et al (2001), where marked adults were recaptured 23Ð 49 km from the release site, but no traps were monitored beyond 49 km. Flight mill studies by Dorhout et al (2008) indicated that 1-d-old unmated females engage in obligate migratory behavior, with maximum distances of Ͼ20 km observed for both males and females. Range and ecotype expansion data (Chiang 1972, Showers 1979, Showers et al 1995 and circumstantial sampling data (Caffrey and Worthley 1927, Colenutt 1995, Bretherton and ChalmersHunt 1989, Langmaid and Young 2006 suggested that European corn borer dispersal can occur up to at least 80 km, but the frequency of dispersal to these distances or beyond has not been determined.…”
mentioning
confidence: 99%